Icelandic Folklore and the Cultural Memory of Religious Change - Bryan, Eric Shane (Arc Humanities Press, 2021)
Iceland’s uncommon proclivity towards storytelling, its robust tradition of medieval manuscripts, and the “re-oralization” of those narratives after the medieval period, create a body of folktales and legends that have encoded a hidden account of how orthodox and heterodox beliefs (sometimes pagan in origin) intermingled as Christianity, and later Reformation, spread through the North. This volume unlocks that secret story by placing Icelandic folktales in a context of religious doctrine, social history, and Old Norse sagas and poetry. The analysis herein reveals a cultural memory of belief. This book is available as Open Access.